Phase angle is related to outcome after ICU admission; an observational study. (February 2018) - Buter, Hanneke; Veenstra, Janny A.; Koopmans, Matty; Boerma, Christiaan E.
Summary: Introduction: Malnutrition at the time of ICU admission is associated with an increased morbidity and mortality. Malnutrition is most often assessed by a questionnaire but can also be determined with bio-impedance and measurement of phase angle. In a single-centre observational study we compared the percentage of malnutrition in patients admitted to our ICU, according to the Short Nutritional Assessment Questionnaire (SNAQ) with the phase angle measured with bio-impedance. Furthermore, we questioned whether malnutrition is related to outcome parameters. Methods: In a 15 week period consecutive patients admitted to the ICU were included. Exclusion criteria included age <18 years, anatomical and/or neurological abnormalities of the limbs and an ICU stay less than 6 h. Bio-impedance measurements were performed shortly after admission, the SNAQ was obtained from the patient or legal representative. Malnutrition is considered with a SNAQ ≥2 or a phase angle of <5° for men and <4.6° for women. The study was approved by our local ethical committee (MCL, nWMO 77, April 18, 2015). Results: 299 Patients were included (66% male, age 66 ± 12 year, BMI 27 ± 4 kg/m 2 and APACHE II score 14 [11–17]), of which 64% elective and 36% acute admissions. Hospital mortality was 7.4%. Malnutrition was present in 16% according to the SNAQ and in 36% according to phase angle. There was a fair accordance between the SNAQ and phase angle. Phase angle was significantly higher in patients with a SNAQ score of 0–1 (5.5°±1.3) in comparison with patients with a SNAQ score ≥2 (4.4°± 1.1) (p < 0.001). Logistic regression analysis showed a significant relation between SNAQ and BMI, malignant disease and hospital length of stay and between phase angle and age, sex, BMI, malignant disease, hospital length of stay and hospital mortality. Conclusion: Malnutrition was present in 16% according to the SNAQ and in 36% according to phase angle in our IC population. Malnutrition was associated with prolonged hospital length of stay. In this small population of mixed ICU patients, a low phase angle was found to independently predict hospital mortality. Clinical Trials.gov number: NCT02911181 .